Spatio-temporal evolutions of ion heat flux and radial electric field during internal transport barrier formation on JT-60U. (4th February 2021) - Kin, F; Itoh, K; Yoshida, M; Honda, M; Kamada, Y; Kamiya, K; Narita, E; Bando, T
Abstract: Spatio-temporal structures of ion heat flux and radial electric field are investigated on JT-60U to understand a mechanism of the internal transport barrier (ITB) formation. Contrary to the conventional argument that the ITB formation is due to the E × B flow shear suppressions on turbulence, we observe that the E × B shearing rate during the ITB formation is not enough for turbulence suppressions with k ρ i ∼ 1. Another finding is that the ITB is formed simultaneously with abrupt decreases of ion heat flux in the global region (like the report in Neudatchine et al 1999 Plasma Phys. Control. Fusion 41 L39), and the gradient–flux relations are non-diffusively developed step by step. These observations suggest the importance of the change in the long-radial fluctuations, which is previously observed in JT-60U (Nazikian et al 2005 Phys. Rev. Lett. 94 135002). Therefore, the model of effects by non-uniformity of the radial electric field, under the condition where the scale separation is violated, is employed to explain such fluctuation quenching. Consistent results are obtained showing that the non-uniformity of the radial electric field effectively works on the fluctuations with long-radial wavelength and increases the temperature gradient. It seems natural that the suppression of the long-radial fluctuations drives the global transport improvement to form the ITB.